A survey of fire debris casework in Canada, 2011–2016. Issue 1 (2nd January 2018) - Sandercock, P. Mark L.
ABSTRACT: A retrospective study of 2723 fire debris samples from 930 cases submitted from across Canada between 1 January 2011 and 31 December 2016 to the RCMP forensic laboratory was conducted. A total of 326 samples of fire debris were not accepted for analysis owing to incorrect or improper packaging and the reasons why these samples were rejected are summarized. Of the 2397 samples from 886 cases accepted for analysis, 63% of the cases had at least one sample that tested positive for an ignitable liquid. Gasoline was the most commonly identified ignitable liquid. While arson is primarily a property-based offence, nearly one quarter (23%) of all arson cases submitted to our laboratory were classified by the investigating agency as a person-based offence; the majority of these cases (84%) were related to a homicide.